2021
DOI: 10.3389/fimmu.2021.605766
|View full text |Cite
|
Sign up to set email alerts
|

Integrating CAR T-Cell Therapy and Transplantation: Comparisons of Safety and Long-Term Efficacy of Allogeneic Hematopoietic Stem Cell Transplantation After CAR T-Cell or Chemotherapy-Based Complete Remission in B-Cell Acute Lymphoblastic Leukemia

Abstract: Patients often undergo consolidation allogeneic hematopoietic stem cell transplantation (allo-HSCT) to maintain long-term remission following chimeric antigen receptor (CAR) T-cell therapy. Comparisons of safety and efficacy of allo-HSCT following complete remission (CR) achieved by CAR-T therapy versus by chemotherapy for B-cell acute lymphoblastic leukemia (B-ALL) has not been reported. We performed a parallel comparison of transplant outcomes in 105 consecutive B-ALL patients who received allo-HSCT after ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 40 publications
3
40
2
Order By: Relevance
“…conducted a parallel comparison of outcomes among patients with B-ALL who received allo-HSCT after achieving CR with CAR-T therapy (n = 27) or chemotherapy (n = 78). The results demonstrated that there were no significant differences in clinical outcomes (OS, LFS, NRM, relapse, and extensive cGVHD) between the two groups, while a higher incidence of II–IV aGVHD (48.1%) and slower platelet engraftment (14 days) were observed in the CAR-T group ( 42 ). In a previous study, Shadman et al.…”
Section: Discussionmentioning
confidence: 88%
“…conducted a parallel comparison of outcomes among patients with B-ALL who received allo-HSCT after achieving CR with CAR-T therapy (n = 27) or chemotherapy (n = 78). The results demonstrated that there were no significant differences in clinical outcomes (OS, LFS, NRM, relapse, and extensive cGVHD) between the two groups, while a higher incidence of II–IV aGVHD (48.1%) and slower platelet engraftment (14 days) were observed in the CAR-T group ( 42 ). In a previous study, Shadman et al.…”
Section: Discussionmentioning
confidence: 88%
“…Combining allo-SCT and CAR-T cells therapy is an attractive area of research to improve the outcomes further. Allo-SCT has been used in several clinical trials after CAR-T cells treatment and showed efficacy and favorable prognosis in R/R B-ALL [ 40 , 41 ]. Considering the high heterogeneity among and within patients, different CAR-T cell products, and continuously improved treatment strategies, consolidative allo-SCT cannot be generalized; however, it is recommended for high-risk r/r B-ALL patients with no history of allo-SCT and achieved MRD-negative CR after anti-CD19 CAR-T therapy [ 41 ].…”
Section: Improving Responsesmentioning
confidence: 99%
“…This has yet to be explored in HL, though is being investigated in cases of B-cell acute lymphoblastic leukemia (B-ALL). In a study of B-ALL patients who had undergone allogeneic transplant, outcomes for those patients who had received CAR T cells as a bridge to transplant compared similarly to those receiving chemotherapy when looking at NRMrates, leukemia-free survival, and overall survival [83]. Patients receiving CAR T cells ahead of transplant did however have a higher incidence of acute graft versus host disease (grade II only) and chronic graft versus host disease, highlighting a potential negative effect of modulating the immune system ahead of transplant.…”
Section: Interplay Of Transplant and Car T Therapymentioning
confidence: 99%